The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Participant Evaluation of a Multi-disciplinary Oncology Preceptorship Training Program for Oncology Health Professionals from Kumasi, Ghana - Kenneth W. Merrell; Thomas Okpoti Konney; Osei Acheamfour; Joseph Lucido; Abena Yeboah Aduse-Poku; Amanika Kumar; Mavis Bobie Ansah; Adu Tutu Amankwa; Dean Shumway; Fred Kwame Awittor; Augustina Badu-Peprah; Lionel Aurelien A. Kankeu Fonkoua; et al. (Journal of Cancer Education, 2024)
A critical shortage of skilled healthcare workers is a primary cause of disparate global cancer outcomes. We report participant evaluation of a multidisciplinary preceptorship program. In collaboration with the city of Kumasi, Ghana, Mayo Clinic and the City Cancer Challenge hosted a preceptorship program for comprehensive multidisciplinary breast and cervix cancer training. A total of 14 healthcare workers from Kumasi received two weeks of training at Mayo Clinic in November and December 2021. Each participant and preceptor were requested to complete an anonymous post-participation survey. Of the 14 trainee participants, 10 (71%) completed the survey. All respondents found the program “valuable and applicable to their clinical practice.” Ninety percent reported they were able to “review effective and critical elements in the development and expansion of the multidisciplinary team” and able to “solve practical clinical cases as a team”. General themes of satisfaction included: (1) organization and administration, (2) clinical observations and demonstrations, (3) guidelines development, and (4) recognizing the central importance of cultivating a team-based approach. Of the 40 preceptors, 16 (40%) completed the survey. All respondents reported they felt the training would meaningfully “influence patient care in Ghana”, that participation “added value or joy to their clinical practice,” and all wished to “participate in future preceptorship programs”. After a focused two-week program, trainees reported high satisfaction, usefulness from observing specialized cancer care, and value in closely observing a multidisciplinary oncology team. Preceptors reported the experience added joy and perspective to their clinical practice and wished to participate in future programs.

Southern Flounder: Major Milestones and Remaining Knowledge Gaps in Their Biology, Ecology, and Fishery Management - Stephen R. Midway; Frederick S. Scharf; Michael A. Dance; Nancy J. Brown-Peterson; Joseph C. Ballenger; Nicolette S. Beeken; Russell J. Borski; Tanya L. Darden; Kenneth A. Erickson; Troy M. Farmer; Ashley Fincannon; John Godwin; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Mechanisms and shapes of causal exposure-response functions for asbestos in mesotheliomas and lung cancers - Louis Anthony Cox; Kenneth T. Bogen; Rory Conolly; Uschi Graham; Suresh Moolgavkar; Günter Oberdörster; Victor L. Roggli; Francesco Turci; Brooke Mossman (Environmental Research, 2023)

Great expectations: patients’ preferences for clinically significant results from genomic sequencing - Salma Shickh; Agnes Sebastian; Marc Clausen; Chloe Mighton; Christine Elser; Andrea Eisen; Larissa Waldman; Seema Panchal; Thomas Ward; June C. Carroll; Emily Glogowski; Kasmintan A. Schrader; et al. (Human Genetics, 2023)

Correction to: Partial body cryotherapy exposure drives acute redistribution of circulating lymphocytes: preliminary findings - Catriona L. Rose; Helen McGuire; Kenneth Graham; Jason Siegler; Barbara Fazekas de St Groth; Corinne Caillaud; Kate M. Edwards (European Journal of Applied Physiology, 2023)

Partial body cryotherapy exposure drives acute redistribution of circulating lymphocytes: preliminary findings - Catriona L. Rose; Helen McGuire; Kenneth Graham; Jason Siegler; Barbara Fazekas de St Groth; Corinne Caillaud; Kate M. Edwards (European Journal of Applied Physiology, 2023)
Partial body cryotherapy (PBC) is proposed to alleviate symptoms of exercise-induced muscle damage (EIMD) by reducing associated inflammation. No studies have assessed acute PBC exposure on peripheral blood mononuclear cell mobilisation or compared these with cold water immersion (CWI), which may inform how PBC impacts inflammatory processes. This trial examined the impact of a single PBC exposure on circulating peripheral blood mononuclear cells compared to CWI or a control. 26 males were randomised into either PBC (3 min at − 110 to − 140 °C), CWI (3 min at 9 °C), or control (3 min at 24 °C), with blood samples, heart rate, and blood pressure taken before and after exposure. Cytometric analysis determined that CD8 + T-cell populations were significantly elevated after treatments, with PBC increasing CD8 + T cells to a greater degree than either CWI or CON. Natural killer cell counts were also elevated after PBC, with the increase attributed specifically to the CD56 lo CD16 + cytotoxic subset. This provides the first evidence for the effect of PBC exposure on redistribution of immune cells. An increase in circulating leukocyte subsets such as CD8 + T cells and CD56 lo CD16 + natural killer cells suggests that PBC may induce a transient mobilisation of lymphocytes. PBC may thus enable a more efficient trafficking of these cells from the circulation to the site of initial cellular insult from exercise, potentially accelerating the process of cellular recovery. This provides novel evidence on the use of PBC as a recovery treatment and may also have applicability in other clinical settings involving the recovery of damaged skeletal muscle.

Correction to: Cancer Risk and Diesel Exhaust Exposure Among Railroad Workers - Paul E. Rosenfeld; Kenneth R. Spaeth; Ryan Hallman; Rachel Bressler; Graham C. Smith (Water, Air, & Soil Pollution, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Cancer Risk and Diesel Exhaust Exposure Among Railroad Workers - Paul E. Rosenfeld; Kenneth R. Spaeth; Ryan Hallman; Rachel Bressler; Graham C. Smith (Water, Air, & Soil Pollution, 2022)
Inhalation exposure to diesel exhaust in the railroad work environment causes significant and quantifiable cancer risks to many railroad workers. Diesel exhaust has been identified as a known human carcinogen by the International Agency for Research on Cancer (“IARC”) and as a potential carcinogen by the United States Environmental Protection Agency (“USEPA”), the California Environmental Protection Agency’s Office of Environmental Health Hazard Assessment (“OEHHA”), and the National Institute for Occupational Safety & Health (“NIOSH”). Peer-reviewed literature defines the ambient air concentrations of diesel exhaust for several railroad occupations as being above environmental background levels. This study uses diesel exhaust concentrations in the railroad work environment in conjunction with the USEPA’s Integrated Risk Information System (“IRIS”) risk assessment methodology to quantify the cancer risk posed to railroad workers due to occupational inhalation exposure to diesel exhaust. NIOSH Bulletin 68 (2017) states that there is “no known safe level” of exposure to carcinogens and recommends an evaluation of the USEPA’s IRIS guidance to evaluate quantitative risk assessment of human exposure to occupational carcinogens. This is the first study to utilize USEPA methodology to calculate the excess lung cancer risk caused by railroad workers’ cumulative exposure to diesel exhaust.

Spatial scaling of plant and bird diversity from 50 to 10,000 ha in a lowland tropical rainforest - Richard J. Hazell; Kryštof Chmel; Jan Riegert; Luda Paul; Brus Isua; Graham S. Kaina; Pavel Fibich; Kenneth Molem; Alan J. A. Stewart; Mika R. Peck; George D. Weiblen; Vojtech Novotny (Oecologia, 2021)
While there are numerous studies of diversity patterns both within local communities and at regional scales, the intermediate scale of tens to thousands of km 2 is often neglected. Here we present detailed local data on plant communities (using 20 × 20 m plots) and bird communities (using point counts) for a 50 ha ForestGEO plot in lowland rainforest at Wanang, Papua New Guinea. We compare these local diversity patterns with those documented in the surrounding 10,000 ha of lowland rainforest. Woody plant species richness was lower within 50 ha (88% of 10,000 ha richness), even when both were surveyed with identical sampling effort. In contrast, bird communities exhibited identical species accumulation patterns at both spatial scales. Similarity in species composition (Chao-Jaccard) remained constant while similarity in dominance structure (Bray–Curtis) decreased with increased distance between samples across the range from < 1 to 13.8 km for both plant and bird communities. The similarity decay was more rapid in plants, but in both cases was slow. The results indicate low to zero beta-diversity at the spatial scale represented here, particularly for birds but also for woody plants. A 50 ha plot provided a highly accurate representation of broader-scale diversity and community composition within 10,000 ha for birds, and a relatively good representation for woody plants. This suggests potential for wider generalization of data from ForestGEO plots which are almost always locally unreplicated, at least for those in lowland tropical forest.

Container Closure and Delivery Considerations for Intravitreal Drug Administration - Ashwin C. Parenky; Saurabh Wadhwa; Hunter H. Chen; Amardeep S. Bhalla; Kenneth S. Graham; Mohammed Shameem (AAPS PharmSciTech, 2021)
Intravitreal (IVT) administration of therapeutics is the standard of care for treatment of back-of-eye disorders. Although a common procedure performed by retinal specialists, IVT administration is associated with unique challenges related to drug product, device and the procedure, which may result in adverse events. Container closure configuration plays a crucial role in maintaining product stability, safety, and efficacy for the intended shelf-life. Careful design of primary container configuration is also important to accurately deliver small volumes (10-100 μL). Over- or under-dosing may lead to undesired adverse events or lack of efficacy resulting in unpredictable and variable clinical responses. IVT drug products have been traditionally presented in glass vials. However, pre-filled syringes offer a more convenient administration option by reducing the number of steps required for dose preparation there by potentially reducing the time demand on the healthcare providers. In addition to primary container selection, product development studies should focus on, among other things, primary container component characterization, material compatibility with the formulation, formulation stability, fill volume determination, extractables/leachables, and terminal sterilization. Ancillary components such as disposable syringes and needles must be carefully selected, and a detailed administration procedure that includes dosing instructions is required to ensure successful administration of the product. Despite significant efforts in improving the drug product and administration procedures, ocular safety concerns such as endophthalmitis, increased intraocular pressure, and presence of silicone floaters have been reported. A systematic review of available literature on container closure and devices for IVT administration can help guide successful product development.

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

The good, the bad, and the ugly of environmental quality benchmarks: EQSPAE-2016 dedicated to Dr. Peter Michael Chapman (1951–2017) - Kenneth M. Y. Leung; Graham Merrington; Michael St. J. Warne; Richard J. Wenning; Fengchang Wu (Environmental Science and Pollution Research, 2018)

Regional climate changes drive increased scaled-chrysophyte abundance in lakes downwind of Athabasca Oil Sands nitrogen emissions - Graham R. Mushet; Kathleen R. Laird; Biplob Das; Brittany Hesjedal; Peter R. Leavitt; Kenneth A. Scott; Gavin L. Simpson; Björn Wissel; Jared D. Wolfe; Brian F. Cumming (Journal of Paleolimnology, 2017)

Longer exercise duration delays post-exercise recovery of cardiac parasympathetic but not sympathetic indices - Scott Michael; Ollie Jay; Kenneth S. Graham; Glen M. Davis (European Journal of Applied Physiology, 2017)

The Microbiota, Immunoregulation, and Mental Health: Implications for Public Health - Christopher A. Lowry; David G. Smith; Philip H. Siebler; Dominic Schmidt; Christopher E. Stamper; James E. Hassell; Paula S. Yamashita; James H. Fox; Stefan O. Reber; Lisa A. Brenner; Andrew J. Hoisington; Teodor T. Postolache; et al. (Current Environmental Health Reports, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Submaximal exercise intensity modulates acute post-exercise heart rate variability - Scott Michael; Ollie Jay; Mark Halaki; Kenneth Graham; Glen M. Davis (European Journal of Applied Physiology, 2016)

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

Quinolinic acid/tryptophan ratios predict neurological disease in SIV-infected macaques and remain elevated in the brain under cART - Julia L. Drewes; Kelly A. Meulendyke; Zhaohao Liao; Kenneth W. Witwer; Lucio Gama; Ceereena Ubaida-Mohien; Ming Li; Francesca M. Notarangelo; Patrick M. Tarwater; Robert Schwarcz; David R. Graham; M. Christine Zink (Journal of NeuroVirology, 2015)

Operationalizing resilience for adaptive coral reef management under global environmental change - Kenneth R.N. Anthony; Paul A. Marshall; Ameer Abdulla; Roger Beeden; Chris Bergh; Ryan Black; C. Mark Eakin; Edward T. Game; Margaret Gooch; Nicholas A.J. Graham; Alison Green; Scott F. Heron; et al. (Global Change Biology, 2015)
Cumulative pressures from global climate and ocean change combined with multiple regional and local‐scale stressors pose fundamental challenges to coral reef managers worldwide. Understanding how cumulative stressors affect coral reef vulnerability is critical for successful reef conservation now and in the future. In this review, we present the case that strategically managing for increased ecological resilience (capacity for stress resistance and recovery) can reduce coral reef vulnerability (risk of net decline) up to a point. Specifically, we propose an operational framework for identifying effective management levers to enhance resilience and support management decisions that reduce reef vulnerability. Building on a system understanding of biological and ecological processes that drive resilience of coral reefs in different environmental and socio‐economic settings, we present an Adaptive Resilience‐Based management ( ARBM ) framework and suggest a set of guidelines for how and where resilience can be enhanced via management interventions. We argue that press‐type stressors (pollution, sedimentation, overfishing, ocean warming and acidification) are key threats to coral reef resilience by affecting processes underpinning resistance and recovery, while pulse‐type (acute) stressors (e.g. storms, bleaching events, crown‐of‐thorns starfish outbreaks) increase the demand for resilience. We apply the framework to a set of example problems for Caribbean and Indo‐Pacific reefs. A combined strategy of active risk reduction and resilience support is needed, informed by key management objectives, knowledge of reef ecosystem processes and consideration of environmental and social drivers. As climate change and ocean acidification erode the resilience and increase the vulnerability of coral reefs globally, successful adaptive management of coral reefs will become increasingly difficult. Given limited resources, on‐the‐ground solutions are likely to focus increasingly on actions that support resilience at finer spatial scales, and that are tightly linked to ecosystem goods and services.

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Scientific derivation of environmental quality benchmarks for the protection of aquatic ecosystems: challenges and opportunities - Kenneth M. Y. Leung; Graham Merrington; Michael St. J. Warne; Richard J. Wenning (Environmental Science and Pollution Research, 2014)

Water quality guidelines for chemicals: learning lessons to deliver meaningful environmental metrics - Graham Merrington; Youn-Joo An; Eric P. M. Grist; Seung-Woo Jeong; Chuthamat Rattikansukha; Susan Roe; Uwe Schneider; Suthipong Sthiannopkao; Glenn W. Suter; Rick Van Dam; Patrick Van Sprang; Ju-Ying Wang; et al. (Environmental Science and Pollution Research, 2014)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Impact of a simulated oil spill on benthic phototrophs and nitrogen‐fixing bacteria in mudflat mesocosms - Panagiota‐Myrsini Chronopoulou; Anne Fahy; Frédéric Coulon; Sandrine Païssé; Marisol Goñi‐Urriza; Louis Peperzak; Laura Acuña Alvarez; Boyd A. McKew; Tracy Lawson; Kenneth N. Timmis; Robert Duran; Graham J. C. Underwood; et al. (Environmental Microbiology, 2013)
Summary Coastal and estuarine ecosystems are highly susceptible to crude oil pollution. Therefore, in order to examine the resilience of benthic phototrophs that are pivotal to coastal ecosystem functioning, we simulated an oil spill in tidal mesocosms consisting of intact sediment cores from a mudflat at the mouth of the C olne E stuary, UK . At day 21, fluorescence imaging revealed a bloom of cyanobacteria on the surface of oiled sediment cores, and the upper 1.5 cm thick sediment had 7.2 times more cyanobacterial and 1.7 times more diatom rRNA sequences when treated with oil. Photosystem II operating efficiency ( Fq ′ / Fm ′) was significantly reduced in oiled sediments at day 7, implying that the initial diatom‐dominated community was negatively affected by oil, but this was no longer apparent by day 21. Oil addition significantly reduced numbers of the key deposit feeders, and the decreased grazing pressure is likely to be a major factor in the increased abundance of both diatoms and cyanobacteria. By day 5 concentrations of dissolved inorganic nitrogen were significantly lower in oiled mesocosms, likely resulting in the observed increase in nifH ‐containing, and therefore potentially dinitrogen‐fixing, cyanobacteria. Thus, indirect effects of oil, rather than direct inhibition, are primarily responsible for altering the microphytobenthos.

W olbachia in a major African crop pest increases susceptibility to viral disease rather than protects - Robert I. Graham; David Grzywacz; Wilfred L. Mushobozi; Kenneth Wilson (Ecology Letters, 2012)
W olbachia are common vertically transmitted endosymbiotic bacteria found in S podoptera exempta ), which show that the prevalence and intensity of infection with a nucleopolydrovirus ( SpexNPV ) is positively associated with infection with three strains of W olbachia . We also use laboratory bioassays to demonstrate that infection with one of these strains, a male‐killer, increases host mortality due to SpexNPV by 6–14 times. These findings suggest that rather than protecting their lepidopteran host from viral infection, W olbachia instead make them more susceptible. This finding potentially has implications for the biological control of other insect crop pests.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Lack of effect of hydrochlorothiazide and low-dose aspirin on the renal clearance of urate and oxypurinol after a single dose of allopurinol in normal volunteers - Daniel Y. Ng; Sophie L. Stocker; Garry G. Graham; Kenneth M. Williams; Richard O. Day (European Journal of Clinical Pharmacology, 2011)

A FRUITFULL-like gene is associated with genetic variation for fruit flesh firmness in apple (Malus domestica Borkh.) - Volkan Cevik; Carol D. Ryder; Alexandra Popovich; Kenneth Manning; Graham J. King; Graham B. Seymour (Tree Genetics & Genomes, 2010)

Climate‐related, decadal‐scale assemblage changes of seagrass‐associated fishes in the northern Gulf of Mexico - F. JOEL FODRIE; KENNETH L. HECK; SEAN P. POWERS; WILLIAM M. GRAHAM; KELLY L. ROBINSON (Global Change Biology, 2010)
Global temperatures are rising, and are expected to produce a poleward shift in the distribution of many organisms. We quantified changes in fish assemblages within seagrass meadows of the northern Gulf of Mexico (GOM) between the 1970s and 2006–2007, and observed changes consistent with this forecast. During 2006–2007 we sampled seagrass meadows using the same gears and methods previously employed by R. J. Livingston in coastal waters of northwest Florida throughout the 1970s. Comparisons between datasets revealed numerous additions to the fish fauna during 2006–2007 that were completely absent in the 1970s, including: Lutjanus synagris (lane snapper), Epinephelus morio (red grouper), Chaetodon ocellatus (spotfin butterflyfish), Mycteroperca sp (grouper, non gag), Centropristis philadelphica (rock sea bass), Fistularia tabacaria (bluespotted cornetfish), Ocyurus chrysurus (yellowtail snapper), Thalassoma bifasciatum (bluehead wrasse), Abudefduf saxatilis (sergeant major), Acanthuridae spp. (surgeonfishes) and Sparisoma viride (stoplight parrotfish). Several other species showed large increases in abundance during the interval between 1979 and 2006, including Mycteroperca microlepis (gag grouper, up ∼200 ×), Lutjanus griseus (gray snapper, up ∼105 ×), and Nicholsina usta (emerald parrotfish, up ∼22 ×). All of these are tropical or subtropical species that now make up a greater percentage of seagrass‐associated fish assemblages in the northern GOM than in the past. Additionally, we observed regional increases in air and sea surface temperatures (> 3 °C) during the ∼30 years that separate Livingston's samples and ours that correlate with northern shifts in the distribution of warm‐water fishes. Documenting these range shifts is a critical first step in investigating the consequences of global warming for endemic marine communities and fishery production in the northern GOM.

Hydrochemical fluctuations and crustacean community composition in an ephemeral saline lake (Sua Pan, Makgadikgadi Botswana) - Graham Paul McCulloch; Kenneth Irvine; Frank D. Eckardt; Rob Bryant (Hydrobiologia, 2008)

Lipoxygenase metabolism: roles in tumor progression and survival - Graham P. Pidgeon; Joanne Lysaght; Sriram Krishnamoorthy; John V. Reynolds; Ken O’Byrne; Daotai Nie; Kenneth V. Honn (Cancer and Metastasis Reviews, 2007)

Identification of novel small RNAs in tomato (Solanum lycopersicum) - Rachel L. Rusholme Pilcher; Simon Moxon; Nima Pakseresht; Vincent Moulton; Kenneth Manning; Graham Seymour; Tamas Dalmay (Planta, 2007)

An assessment of European pig diversity using molecular markers: Partitioning of diversity among breeds - Louis Ollivier; Lawrence Alderson; Gustavo C. Gandini; Jean-Louis Foulley; Chris S. Haley; Ruth Joosten; Annemieke P. Rattink; Barbara Harlizius; Martien A. M. Groenen; Yves Amigues; Marie-Yvonne Boscher; Geraldine Russell; et al. (Conservation Genetics, 2005)

The Biodiversity and Conservation of Saproxylic Diptera In Scotland - Graham E. Rotheray; Geoff Hancock; Steve Hewitt; David Horsfield; Iain MacGowan; David Robertson; Kenneth Watt (Journal of Insect Conservation, 2001)

Transcriptional profiling of human microvascular endothelial cells in the proliferative and quiescent state using cDNA arrays - Hua-Tang Zhang; Michael Gorn; Kenneth Smith; Andrew P. Graham; Kelvin K.W. Lau; Roy Bicknell (Angiogenesis, 1999)